Analysis Marketing Strategy Of Phenom Event Indonesia During The Covid-19 Pandemic - Halim, Deddy Kurniawan; Pramesti, Dinar Sukma; Ratnasari, Heidy (Politeknik Internasional Bali, 2023)
The MICE industry is one of the tourism industries affected by covid-19 pandemic. Phenom Event Indonesia (PEI) is one of the EOs engaged in the field of MICE organizing services which have also been affected by the co-19 pandemic. It's just that, they have implemented the right marketing strategy so that the impact of the pandemic does not make PEI go out of business. This study aims to analyze the marketing strategy used by PEI to maintain its company during a pandemic. The research method uses qualitative research methods. Data obtained through interviews, literature studies and internet studies. The theory used is marketing theory which consists of product, price, place, and promotion. The results of the study reveal that the marketing strategy used by PEI to survive in the midst of the covid-19 pandemic, namely by: 1) Products, namely by offering new virtual hybrid studio products and equipping themselves with CHSE certificates, 2) The pricing strategy used by PEI is to adjust the scale events and budgets provided from clients with a negotiation process, 3) Location Strategy by utilizing PEI's strategic offices to become restaurants, bars and pubs that can be used for small-scale event venues, 4) Judging from PEI's promotion using digital marketing with a YouTube account and sales calls to all repeater clients as well as changing the target market and always providing feedback in the form of souvenirs or gifts to clients. It is hoped that the results of the research can be used as reference material for EO's marketing strategy when facing pandemics in the future.